Sales Management Control Strategies in Banking Strategic Fit and Performance Impact - Mueller, Florian; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
Not only have the global financial crisis, a changing regulatory environment, increasing competitive pressure, and changes in customer behavior created an overall difficult environment for banking institutions, but they have also increased the pressure on their sales performance. Based on the results of 300 interviews with sales executives of banks in Germany, Florian Mueller empirically investigates how retail, private, and corporate banking institutions need to set up their sales management control strategy in accordance to their specific environment, business strategy, and organizational characteristics in order to increase performance.
Keywords: Economics; Banks and banking; Economics/Management Science; Finance /Banking.